Unveiling Semantics: A Multifaceted Analysis of Emotion, Prosody, and Artistry in Nizar Qabbani's Elegy - Albatool Abalkheel; Maha Sourani (Kurdish Studies, 2022)
Qabbani's oeuvre left indelible marks on Arabic literature, sparking fervent debates and critical discourse. No previous work has explicitly tackled the question of syllable prosody in Balqis nor the heartbeat's intricate correlation of sounds in Qabbani’s emotional state as this qualitative analytical study does. To collect data, the Speech Rate Meter and the Emotionality Meter software were used to demonstrate the presence of 62 accessible syllables recited within a 24-second interval, in contrast to the typical 228 vocal clips produced by a healthy individual per minute. Additionally, the poet's heart rate during the recitation of the first stanza was approximately 52 beats/minute, deviating from the expected 76 beats/minute for healthy individuals. Furthermore, when examining the ratio of segments in the closing lines/minute, it was found that they yielded 164 segments (99 long, 53 open, 46 closed, 65 short) with 55 heartbeats/minute. The analysis also revealed the presence of over 50+ syllables within the poem, indicating the poet's fatigue, which hindered his ability to maintain the fluency of certain phonetic elements. Consequently, these syllables transitioned from independent, short segments into subdued, silent sounds, incorporated within longer segments. Finally, recommendations for future research are offered to provide a basis for upcoming studies.